Gender Equality and the Intersectional Turn - Thorgerdur Einarsdóttir (The Royal Danish Library, 2007)
The article explores recent theoretical debates on intersectionality and gender equality. It addresses problems and potentialities of the emerging ‘equality for all’ policies, drawing upon empirical examples from equality work in Iceland (equal opportunities workers, minority groups, the City of Reykjavik and the University of Iceland). Practical equality work will be viewed through the lenses of feminist theories on ntersectionality and related to wider political context and gender discourse in Iceland. These empirical examples are analyzed in light of the theoretical background, in particular, the different models, discussed by Verloo (2006) and Squires (2005) regarding how practical equality work can be dealt with. By bringing together theory and praxis, light will be shed on some of the problems and possibilities that are bound up with the different approaches.